2019
DOI: 10.1002/aisy.201970070
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Metal Gallium Micromachines Speed Up in Confining Channels

Abstract: Liquid Metal Micromachines In article number http://doi.wiley.com/10.1002/aisy.201900064, Changyong Gao, Qiang He, and co‐workers study the effect of confinement on the motion behavior of the liquid metal gallium machine. In the confining channels, the liquid metal gallium machine shows an adaptive deformation and speed‐up motion upon applying a direct current electric field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Wang et al reported a Galinstan micromotor moved at a speed of 117.2 mm/s after applying a DC electric field with a voltage of 30 V [ 41 ]. These MLMTs can adaptively and automatically deform and accelerate in narrow channels ( Figure 12 A).…”
Section: Propulsion Mechanism Of Mlmtsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al reported a Galinstan micromotor moved at a speed of 117.2 mm/s after applying a DC electric field with a voltage of 30 V [ 41 ]. These MLMTs can adaptively and automatically deform and accelerate in narrow channels ( Figure 12 A).…”
Section: Propulsion Mechanism Of Mlmtsmentioning
confidence: 99%
“…( ii ) The relationship of the deformation degree (L/L 0 ) of MLMTs and its position in the channels. ( iii ) The instantaneous velocity of MLMTs [ 41 ]. ( B ) The schematic representation of the experimental setup and the CEW effect [ 105 ].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…However, these methods are currently hampered by quite complex manufacturing processes. Wang et al used LM gallium to move toward the negative electrode under the impetus of hydrogen bubbles . However, this method usually relies on intense chemical reactions, and bubbles inevitably affect LM droplets.…”
Section: Introductionmentioning
confidence: 99%
“…Soft and stretchable electronics have received a tremendous amount of attention due to their potential for applications in the next generation of electronics such as wearable and conformal electronics, soft robotics, , and stretchable displays. Among various materials, liquid metals, especially gallium and its alloys, have been considered as compelling conductors and fillers due to their inherent stretchability (while maintaining metallic conductivity), low viscosity, and patternability due to the oxide layer spontaneously formed on the surface. Thus, liquid metals have been maneuvered to fabricate high-end flexible and stretchable electronic components and devices such as stretchable antennas, deformable electrodes, , soft sensors, switches, , actuators, and micromachines. …”
Section: Introductionmentioning
confidence: 99%